Means-Tested Welfare Benefits and Subjective Well-Being Through Time: Does Clients' Life Satisfaction Recover? - Nivorozhkin, Anton; Promberger, Markus (Social Policy & Administration, 2024)
We study the process of subjective well-being adaptation to receiving welfare benefits. Using 15 waves of the German Panel Study Labour Market and Social Security and fixed-effects regression models, we find that welfare benefit receipt decreases life satisfaction. Furthermore, on average, the results speak against the hypothesis of adaptation to receiving the benefit; the subjective well-being of welfare benefit receipt starts poor and stays poor. On average, the life satisfaction of women with small children does not decrease upon receipt of welfare benefits.
CRIS-Team Scopus Importer:2024-08-30
Keywords: life satisfaction; means-test; subjective well-being; welfare benefits